43rd Penang Annual Round Island Relay December 10, 2023 / Assoc Prof Dr Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2024)
A total of 44 teams took part in the 2023 Penang Annual Round Island Relay. The relay run was divided into 3 categories: Men's Open, Men's Veteran, and Mixed Team. Each team consisted of 12 members and changed the baton at 11 exchange zones around the island (please refer to the map). Participants in the Men's Open and Men's Veteran categories were all male, while members of each Mixed Team comprised of six males and six females. The teams registered for the event were labelled from Team 1 to Team 14 in the Men's Open category, from Team 15 to Team 30 in the Men's Veteran category, and from Team A to Team S in the Mixed Team category. I participated as one of the referees for the Men's Veteran category and was stationed at the Balik Pulau exchange zone. At this station, the fourth runner had to pass the baton to the fifth runner.